Diaspora, identity, and religion : new directions in theory and research - Kokot, Waltraud; Tölölyan, Khachig; Alfonso, Carolin, 1969- (Transnationalism. Routledge research in transnationalism, 2004)
Examines the development of the concept of diaspora and new perspectives on global networks and local identities. Features case histories on the Caribbean, Irish, Irish-American, Armenian, African and Greek diasporas.